2018
DOI: 10.3390/info9040094
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble of Condition Based Classifiers for Device Independent Detailed Human Activity Recognition Using Smartphones †

Abstract: Human activity recognition is increasingly used for medical, surveillance and entertainment applications. For better monitoring, these applications require identification of detailed activity like sitting on chair/floor, brisk/slow walking, running, etc. This paper proposes a ubiquitous solution to detailed activity recognition through the use of smartphone sensors. Use of smartphones for activity recognition poses challenges such as device independence and various usage behavior in terms of where the smartpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 39 publications
0
15
0
2
Order By: Relevance
“…The first stage of HAR is data collection and filtering. The data collection process begins by defining a set of activities to be recognized, and then recording data from the sensors during a defined activity set [16], or simply taking over data from a publicly available HAR dataset [17].…”
Section: Impact Of Human Activity Recognition (Har) Stages On Enermentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage of HAR is data collection and filtering. The data collection process begins by defining a set of activities to be recognized, and then recording data from the sensors during a defined activity set [16], or simply taking over data from a publicly available HAR dataset [17].…”
Section: Impact Of Human Activity Recognition (Har) Stages On Enermentioning
confidence: 99%
“…Besides different sliding window sizes [64], some researches can also choose to introduce window overlapping [65]. The most commonly used fixed-size sliding window overlapping size is 1 s (used in [17,21,42,66]).…”
Section: Impact Of Human Activity Recognition (Har) Stages On Enermentioning
confidence: 99%
“…These activities are classified based on feature extraction schemes that are broadly categorized as time and frequency domains. In [19,20,21,22,23,24,25] researchers have implemented the time domain and frequency domain feature extraction as a combined approach. Other researchers in [26,27,28,29,30,31] have used feature extraction in the time domain only, whilst, in [32] researchers applied the frequency domain and time-frequency domain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors in [33] have chosen the time domain, frequency domain and time-frequency domain for feature extraction. Out of these studies, Saha et al [19] found that the ensemble classifier performs best, with an overall accuracy rate of 94% using accelerometer and gyroscope sensor data. In the research carried out by Mohamed et al [20], a combination of accelerometer data from the arm, belt and pocket analysed using rotation forest with the base learner C4.5, was found to provide the best overall classification accuracy rate of 98.9% [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The human activity recognition which is increasingly used for medical, surveillance, and entertainment applications is addressed by the second paper entitled "An Ensemble of Condition Based Classifiers for Device Independent Detailed Human Activity Recognition Using Smartphones", by Jayita Saha, Chandreyee Chowdhury, Ishan Roy Chowdhury, Suparna Biswas, and Nauman Aslam [3]. For better monitoring, human activity applications require identification of detailed activity like sitting on chair/floor, brisk/slow walking, running, etc.…”
mentioning
confidence: 99%